Gene families of cuticular proteins analogous to peritrophins (CPAPs) in Tribolium castaneum have diverse functions - Jasrapuria, Sinu; Specht, Charles A.; Kramer, Karl J.; Beeman, Richard W.; Muthukrishnan, Subbaratnam (My University, 2013)
The functional characterization of an entire class of 17 genes from the red flour beetle, Tribolium castaneum, which encode two families of Cuticular Proteins Analogous to Peritrophins (CPAPs) has been carried out. CPAP genes in T. castaneum are expressed exclusively in cuticle-forming tissues and have been classified into two families, CPAP1 and CPAP3, based on whether the proteins contain either one (CPAP1), or three copies (CPAP3) of the chitin-binding domain, ChtBD2, with its six characteristically spaced cysteine residues. Individual members of the TcCPAP1 and TcCPAP3 gene families have distinct developmental patterns of expression. Many of these proteins serve essential and non-redundant functions in maintaining the structural integrity of the cuticle in different parts of the insect anatomy. Three genes of the TcCPAP1 family and five genes of the TcCPAP3 family are essential for insect development, molting, cuticle integrity, proper locomotion or fecundity. RNA interference (RNAi) targeting TcCPAP1-C, TcCPAP1-H, TcCPAP1-J or TcCPAP3-C transcripts resulted in death at the pharate adult stage of development. RNAi for TcCPAP3-A1, TcCPAP3-B, TcCPAP3-D1 or TcCPAP3-D2 genes resulted in different developmental defects, including adult/embryonic mortality, abnormal elytra or hindwings, or an abnormal ‘stiff-jointed’ gait. These results provide experimental support for specialization in the functions of CPAP proteins in T. castaneum and a biological rationale for the conservation of CPAP orthologs in other orders of insects. This is the first comprehensive functional analysis of an entire class of cuticular proteins with one or more ChtBD2 domains in any insect species.
Citation: Jasrapuria S, Specht CA, Kramer KJ, Beeman RW, Muthukrishnan S (2012) Gene Families of Cuticular Proteins Analogous to Peritrophins (CPAPs) in Tribolium castaneum Have Diverse Functions. PLoS ONE 7(11): e49844. doi:10.1371/journal.pone.0049844
Keywords: Tribolium castaneum; Red flour beetle; Cuticular Proteins Analogous to Peritrophins; CPAPs; Chitin; Cuticular proteins